Biochemical Genetic Analysis Of Three Population Of Marble Grouper, Epinephelus polypekhadion - Gusti Ngurah Permana; Haryanti Haryanti; Sari Budi Moria; Nyoman Adiasmara Giri; Ketut Sugama (Universitas Gadjah Mada, 2007)
Genetic variations of marble groupers, Epinephelus polypekhadion were evaluated to know genetic performance of fish to support fish seed production. Fifty fish samples from three locations i.e. West Nusa Tenggara, South Sulawesi and East Java were collected for analysis. Genetic analysis has been examined through allozyme electrophoresis by using 11 enzymes (ADH, GPI, SDH, IDH, LDH, ME, PGM, 6PGD, MPI, SP, EST). The result showed that 16 loci were detected, and three of them were polymorphism enzymes namely Isocitric dehydrogenase (IDH*), Glucose Phosphate Isomerase (GPI-1*) and Esterase (EST-2*). One locus (EST-2) was polymorphic in the East Java and West Nusa Tenggara populations and three loci (EST-2, GPI-1 and IDH) were polymorphic in the South Sulawesi population. The heterozygosity ranged from 0.007 to 0.034. Rogers genetic distance between population pairs were ranged from 0.005 to 0.012 (average = 0.009). Differences between genetic populations were significant (P<0.05). East Java and West Nusa Tenggara populations have same gene pool.